The mobility of oxygen containing species (OCS*) over Pt-based catalyst surfaces: Impact on the oxygen reduction reaction (ORR) activity - Gambu, Thobani G (Department of Chemical Engineering, 2021)
The growing need to curb greenhouse gas emissions has made low-temperature proton exchange membrane fuel cells (PEMFCs) more attractive for automotive application. One of the major problems facing PEMFCs is the sluggish kinetics of the oxygen reduction reaction (ORR). To further enable wide-scale commercialisation of PEMFCs for automotive applications, major improvements in the ORR catalyst are therefore needed. An in depth understanding of the ORR mechanism over Pt surfaces can enable rational approaches in the search for more active ORR catalysts. The ORR occurs over multi-faceted Pt nanoparticles which predominantly expose Pt{111} and Pt{100} facets. Most studies have modelled the overall ORR activity over multi-faceted surface assuming that the Pt{111} and Pt{100} facets are kinetically isolated. Density functional theory (DFT) studies have shown that Pt(111) surfaces can efficiently facilitate OH* hydrogenation to H2O* but not the hydrogenation of O* to OH*, whereas Pt(100) surfaces can facilitate O* hydrogenation to OH* better than OH* hydrogenation to H2O*. If O* intermediates can readily diffuse from Pt{111} to Pt{100} facets and OH* from Pt{100} to Pt{111} facets, the ORR activity on Pt{111} and Pt{100} facets of multi-faceted surfaces may no longer be limited by O* and OH* hydrogenation steps, respectively. This study uses DFT and microkinetic models to investigate the nature of inter-facet cooperation and how it influences the ORR activity under dry conditions, i.e. catalyst surface exposed to a gas mixture of 33% O2 and 67% H2 at 1 bar. Under these conditions, it is assumed that the Langmuir-Hinshelwood kinetics are dominant. Using DFT, the adsorption, diffusion and reaction energetics of various reaction intermediates and reaction steps were calculated. The Pt{111} and Pt{100} facets were modelled as Pt(111)-p(3x3) and Pt(100)-p(3x3) slabs, respectively. The edge was modelled using a rhombic nanowire model with alternating Pt{111} and Pt{100} facets. Edge sites were found to adsorb oxygen containing species strongly. Consequently, the diffusion barriers of O* and OH* from edge sites towards terrace sites were much higher than the diffusion on the terraces and even higher than the activation barrier for reaction in the ORR. Replacing the edge Pt atoms with Au and Ag atoms weakens the adsorption of both O* and OH* on edge sites. Microkinetic analyses of ORR requires the inclusion of lateral interactions, since otherwise a full coverage of the surface with O* is predicted. Higher ORR rates are obtained on Pt(100) surfaces and --(vi)-- Pt{100} facets than on Pt(111) surfaces and Pt{111} facets. The ORR activity on Pt(111) and Pt(100) is limited by O* hydrogenation at T < 480 K and O2* dissociation at high temperatures. The ORR pathway varies greatly over these surfaces. On Pt(111), the ORR follows a peroxyl pathway at T < 500 K and a dissociative pathway at T > 700 K. On Pt(100) surface H2O* is formed via O* hydrogenation to OH* followed by 2OH* coupling to H2O* and O*. The ORR activity on multifaceted Pt surfaces was shown to be dependent on the ratio of edge sites to Pt{111} sites Modelling the inter-facet exchange of ORR intermediates based on data generated using Au and Ag modified nanowires could improve inter-facet cooperation. The most interesting case was Ag modified systems where inter-facet exchange of OH* occurs at temperatures as low as 360 K. On these systems, the ORR pathway on Pt{111} involves OH* diffusion from edge followed by OH* hydrogenation to H2O*. No O2 adsorbs on the Pt{111} facet. Edge modification has the ability to selectively enable inter-facet exchange of some reaction intermediates whilst inhibiting others. Therefore, it should be explored in rational catalyst design.